Public incentives, private investment, and outlooks for hybrid rice in Bangladesh and India - Spielman, David J.; Ward, Patrick S.; Kolady, Deepthi Elizabeth; Ar-Rashid, Harun (Wiley, 2017)
The governments of Bangladesh and India have set impressive targets to expand hybrid rice cultivation as part of their national food security strategies for the next decade. Although hybrid rice offers significant yield improvements over varietal rice, adoption by farmers remains low and unstable. This paper analyzes the technical challenges, market opportunities, and policy constraints associated with hybrid rice in both countries. It argues that while many of the technical constraints can be addressed through continued investment in breeding, significant challenges remain relating to product development, marketing, and economic policy. Solutions require new insight into relationships between industry structure, business strategies, and public policy incentives.